2021
DOI: 10.1097/md.0000000000027438
|View full text |Cite
|
Sign up to set email alerts
|

The impact of venous resection in pancreatoduodectomy

Abstract: Background: Vein resection pancreatoduodenectomy (VRPD) may be performed in selected pancreatic cancer patients. However, the main risks and benefits related to VRPD remain controversial. Objective: This review aimed to evaluate the risks and survival benefits that the VRPD may add when compared with standard pancreatoduodenectomy (PD). Methods: A systematic review and meta-analysis of studies comparing VRPD and PD were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“… 47 - 51 Compared with pancreatic resection alone, adding SMV-PV resection significantly increased 30-day postoperative mortality, 47 , 50 but not 90-day mortality, 51 morbidity, 47 , 50 the rates of certain complications, 48 , 51 the length of hospital stay, 48 or the proportion of non-radical resections. 47 - 51 Long-term survival was also significantly shorter for patients undergoing SMV-PV resection. 47 , 49 - 51 …”
Section: Vascular Resectionmentioning
confidence: 95%
See 2 more Smart Citations
“… 47 - 51 Compared with pancreatic resection alone, adding SMV-PV resection significantly increased 30-day postoperative mortality, 47 , 50 but not 90-day mortality, 51 morbidity, 47 , 50 the rates of certain complications, 48 , 51 the length of hospital stay, 48 or the proportion of non-radical resections. 47 - 51 Long-term survival was also significantly shorter for patients undergoing SMV-PV resection. 47 , 49 - 51 …”
Section: Vascular Resectionmentioning
confidence: 95%
“… 47 - 51 Long-term survival was also significantly shorter for patients undergoing SMV-PV resection. 47 , 49 - 51 …”
Section: Vascular Resectionmentioning
confidence: 96%
See 1 more Smart Citation
“…In high-volume centers, type 2 PD with venous resection of the portomesenteric veins is expected to account for at least 15% of pancreatic resections (63). Recent meta-analysis reinforces that venous resection is associated with worse short-term outcomes, such as increased blood loss, perioperative morbidity and higher positive margins as well as lower long-term survival (64,65). Although high heterogeneity and different levels of center experience will always be an inherent challenge in this type of comparison.…”
Section: Extended Pancreatoduodenectomy-venous Managementmentioning
confidence: 99%
“…A recent meta-analysis by Filho et al [ 52 ] confirmed that PDVR was associated with a higher risk for postoperative morbidity and mortality, longer duration of hospitalization, and higher blood loss as well as a worse OS compared with standard PD.…”
Section: Venous Resectionsmentioning
confidence: 99%